2022
DOI: 10.1523/jneurosci.2097-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Medial Orbitofrontal–Striatal Circuits Support Dissociable Component Processes of Risk/Reward Decision-Making

Abstract: The medial orbitofrontal cortex (mOFC) regulates a variety of cognitive functions, including refining action selection involving reward uncertainty. This region sends projections to numerous subcortical targets, including the ventral and dorsal striatum, yet how these corticostriatal circuits differentially regulate risk/reward decision-making is unknown. The present study examined the contribution of mOFC circuits linking the nucleus accumbens (NAc) and dorsomedial striatum (DMS) to risk/ reward decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 99 publications
2
11
0
Order By: Relevance
“…Indeed, other evidence suggests that VO is required for response inhibition but specifically in value learning when outcomes are not easily predicted or in situations of delay uncertainty ( Meyer and Bucci, 2016 ; Hardung et al, 2017 ; Stolyarova and Izquierdo, 2017 ). Less activation in the MO is consistent with a more substantial role of this subregion and its target areas (ventral striatum and nucleus accumbens) in choice impulsivity (delay and probabilistic discounting) and with the fact that MO is required for maintaining a memory of reward value to guide actions in situations of uncertain outcomes ( Bradfield et al, 2015 ; Dalton et al, 2016 ; Wang et al, 2019 ; Jenni et al, 2022 ), conditions not explicitly tested in our experiments. Integrating anatomical and functional observations, it has been suggested that more medial subregions of rat OFC provide affective and motivational contributions to decision-making, whereas lateral subregions support sensory integration (i.e., associations of stimuli/cues and sensory events to outcomes) ( Izquierdo, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, other evidence suggests that VO is required for response inhibition but specifically in value learning when outcomes are not easily predicted or in situations of delay uncertainty ( Meyer and Bucci, 2016 ; Hardung et al, 2017 ; Stolyarova and Izquierdo, 2017 ). Less activation in the MO is consistent with a more substantial role of this subregion and its target areas (ventral striatum and nucleus accumbens) in choice impulsivity (delay and probabilistic discounting) and with the fact that MO is required for maintaining a memory of reward value to guide actions in situations of uncertain outcomes ( Bradfield et al, 2015 ; Dalton et al, 2016 ; Wang et al, 2019 ; Jenni et al, 2022 ), conditions not explicitly tested in our experiments. Integrating anatomical and functional observations, it has been suggested that more medial subregions of rat OFC provide affective and motivational contributions to decision-making, whereas lateral subregions support sensory integration (i.e., associations of stimuli/cues and sensory events to outcomes) ( Izquierdo, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…Although we have focused on OFC in this study, it is important to acknowledge that other brain regions also play an important role in the control of motor impulsivity. For example, basolateral amygdala, which has bidirectional connections with OFC, dorsal and ventral striatum, which are important OFC efferent targets, ventromedial prefrontal cortex, and subthalamic nucleus have all been implicated in the control of motor impulsivity ( Muir et al, 1996 ; Dalley et al, 2002 ; Eagle and Baunez, 2010 ; Donnelly et al, 2015 ; Jenni et al, 2022 ). Recently, a claustrum-mPFC pathway has been shown to regulate impulsive responding in the 5-CSRTT ( Liu et al, 2019 ), Thus, future experiments targeting subpopulations of neurons in the OFC and/or projection-specific input and output pathways, as well as other non-OFC areas, will provide a more refined understanding of the circuits and systems underlying the regulation of motor impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Jenni and colleagues ( Jenni et al, 2022 ) reported that MO-to-nucleus accumbens projections are necessary to establish and crystalize choice strategy during tasks that assess risky decision-making. Meanwhile, MO-to-dorsomedial striatum projections are necessary for shifting strategies, such that inactivation caused rats to persist in familiar response sequences even when not profitable, reminiscent of response patterns reported here.…”
Section: Discussionmentioning
confidence: 99%
“…MO function has become clearer in recent years, owing to experiments using inducible and projection-specific manipulations ( Jenni et al, 2022 ; Lichtenberg et al, 2021 ; Loh et al, 2022 ; Malvaez et al, 2019 ). Other investigators have unveiled local neurotransmitter systems necessary for motivated responding ( Jenni et al, 2021 ; Münster et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These projections regulate the risk-reward decision-making where the disruption of the OFC → NAc circuit leads to impaired patters of choice and OFC → DST adjust choice to changes in profitability. 44 In the basolateral amygdala (BLA), genetically and spatially distinct neuronal populations are activated by rewarding and aversive stimuli respectively, with the latter projecting to the NAc. 45 It is also a part of a positive feedback loop comprising VTA-BLA-NAc, which is activated by sex reward and inhibited by VTA's GABAergic neurons.…”
Section: Neural Reward Centers and Signalsmentioning
confidence: 99%